Temporal and spatial distribution of the commercial shrimp Litopenaeus schmitti (Dendrobranchiata: Penaeidae) in the south-eastern Brazilian coast. (August 2014) - Bochini, Gabriel L.; Fransozo, Adilson; Castilho, Antonio L.; Hirose, Gustavo L.; Costa, Rogerio C.
<x content-type="archive" xml:space="preserve">Abstract</x> The goal of the present study was to assess the temporal and spatial distribution of L. schmitti in three bays of the northern coast of the State of São Paulo, Ubatumirim (UBM), Ubatuba (UBA) and Mar Virado (MV), over a period of two years (1998 and 1999). Abiotic factors were monitored to test their influence on the distribution of the species through redundancy analysis. The shrimp were captured using a commercial fishing boat equipped with double-rig trawling nets at six sampling points. A total of 5658 individuals were collected during the study (4437 and 1221 in the first and second years, respectively). The number of individuals differed between years, bays, seasons and sampling locations. The highest number of L. schmitti was collected in MV (N = 2747), followed by UBM (N = 1649) and UBA (N = 1262). Shrimp abundance correlated positively with organic matter content, salinity and temperature, with the highest number of individuals collected from sites with intermediate levels of organic content (4 and 6%) and increasing when the sediment had a higher proportion of fine and very fine sand + clay. Abundance was also associated negatively with rainfall, given that the analysed population showed a seasonal pattern, with an increase in capture rate in those months following the rainy season. Average rainfall was 222.47 ± 138.68 mm, with a maximum of 538 mm and a minimum of 22.4 mm. The results obtained in this study suggest that, in the region of Ubatuba, temperature, salinity, organic content and rainfall modulate the distribution of these animals.